The Influence of Discipline on the Performance of State Civil Apparatus Mediated by Compensation (Study at the Office of the Ministry of Religion of Tanah Laut Regency) - Zairin Fanzani; Akhmad Abdurahman; Semuel Risal (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to analyze (1) the effect of discipline on compensation, (2) the influence of discipline on Performance, (3) the effect of compensation on Performance, and (4) the influence of discipline on the Performance of the Civil Servant of the Office of the Ministry of Religion of Tanah Laut Regency mediated by compensation. The method used is explanatory. The research population is all ASN in the Office of the Ministry of Religion of Tanah Laut Regency. The sampling technique used is Census taken is 58 people. The process (method) used is a questionnaire. This study's primary data is quantitative data analyzed through regression. The results of the study show: (1) There is a positive and significant influence of discipline on compensation. (2) There is a positive and significant influence of discipline. (3) there is a positive and significant effect of compensation on Performance, and (4) compensation cannot be a mediating variable between Discipline and Performance of Civil Servant at the Office of the Ministry of Religion of Tanah Laut Regency.